(untitled) (European Journal of Pure and Applied Mathematics, 2017)
A GTS (X, µ) is said to be weakly µH-compact if for every µ-open cover Vα : α ∈ ∆ of X there exists a finite subset ∆0 of ∆ such that X ∪cµ(Vα) : α ∈ ∆0 ∈ H. In this paper we study the effect of functions on weakly µH-compact spaces. The main result is that the θ(µ, ν)-continuous image of a weakly µH-compact space is weakly νf(H)-compact